The Influence of WhatsApp Business as a Promotional Media on Interest in Buying Zapoeng Store Products (Generation Z in Cirebon City) - Sunahri, Raden; Raihansyah, Rafly (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The use of smartphones at all times in Generation Z allows business processes to be more effective in creating promotions on social media, plus in daily life, both Generation Z and the older generation more often use the WhatsApp application in their daily lives for communication media, both formal and non-formal. This research discusses the influence of promotional variables carried out by WhatsApp businesses on interest in buying Zapoeng Store products for Generation Z in Cirebon City. This research aims to analyze how much influence WhatsApp business as a promotional medium has on interest in buying Zapoeng Store products for Generation Z in Cirebon City. This research is quantitative research that uses primary data processing, taking a sample of 117 Generation Z respondents in Cirebon City and using data collection techniques in the form of structured interviews. The results of this research state that there is a positive influence between the Whatsapp Business promotion variable and interest in buying Zapoeng Store products for Generation Z in Cirebon City. The significance test states that there is an influence seen from the t table value, and for the determination test which is calculated from calculating the r square formula, that WhatsApp Business as a promotional variable influences the purchase interest variable of Generation Z in Cirebon City by 88%. It can be concluded that the strength of the promotion is a benchmark that must be considered so that the opportunity for interest in purchasing Zapoeng Store products becomes large.